Protective effect and mechanism of fucoidan on intestinal mucosal barrier function in NOD mice. Issue 1 (1st January 2020) - Sun, Ting; Liang, Hui; Xue, Meilan; Liu, Ying; Gong, Anjing; Jiang, Yushan; Qin, Yimin; Yang, Jia; Meng, Danyang
ABSTRACT: This study was to evaluate the protective effect of fucoidan on the intestinal mucosal barrier in non-obese diabetic mice (NOD). Twenty NOD mice were randomly assigned to two groups: the control group and the fucoidan intervention group which were fed with fucoidan at a concentration of 600 mg/kg BW (body weight) per day for five weeks. Mice treated with fucoidan had a significant improvement in glycemic control, and the proportions of Th1/Th2/Th17 cells and the levels of endotoxin, DAO and D-LA were reduced. Fucoidan treatment improved intestinal barrier function by increasing ZO-1, claudin-1 and Occludin protein expression. Moreover, the expression levels of phosphorylated ERK1/2, NF-кB p65 and p38 MAPK were decreased. Our result suggested that pre-treatment with fucoidan could attenuate the inflammatory response and maintain intestinal barrier function in NOD mice. Fucoidan-based functional food may be potential for the prevention of T1DM (type 1 diabetes mellitus).